The experiential construction of mathematics teacher identity and the impact of early mathematical failure - Xenofontos, Constantinos; Andrews, Paul (Frontiers in Education, 2023)
It is broadly accepted that teachers’ professional identities influence how they teach and what their pupils learn. In this paper, drawing on semi-structured interviews with 22 experienced primary teachers from the Republic of Cyprus, we explore the construction of informants’ professional identities with a specific focus on mathematics teaching. Analyses, undertaken according to the constant comparison method, yielded three broad themes, implicated in differing ways in the construction and manifestation of informants’ identities: prior experiences of mathematics, mathematical competence, and images of the self-as-teacher. Overall, teachers fell into two groups, which analyses led us to construe as either mathematical victors or mathematical victims. Mathematical victors had experienced success as learners of school mathematics, from which pleasure, pride, and confidence in their mathematical knowledge for teaching emerged. Their teaching, which emphasised pupils’ attainment of similar enjoyment and success, focused on abstraction and mathematical reasoning. Mathematical victims had experienced failure as learners of school mathematics, from which anxiety and a restricted mathematical knowledge for teaching emerged. Their teaching, which emphasised positive pupil experiences, focused on affect rather than cognition and an avoidance of “traditional” teaching. However, both groups, despite their confident assertions, appeared unaware of the potential of their actions for creating new victims. The findings, which are discussed in relation to existing literature, confirm the complex nature of mathematics teachers’ identities and highlight, in particular, the need for further research into the formative role of teachers’ prior experiences of mathematics, whether positive or negative.